Use of a Tilting Orthopedic Fracture Table to Facilitate Proper Patient Positioning During Intrathecal Neurolysis With Hyperbaric Phenol: A Case Report. Issue 6 (15th September 2017) - Loo, Nathaniel H.; Matchett, Gerald
Abstract : We describe the case of a 41-year-old woman with metastatic cervical cancer and a large mass eroding into the pelvis and left lumbosacral plexus. The patient had intractable left lower extremity pain refractory to standard therapies, and she elected to undergo intrathecal neurolysis. A diagnostic intrathecal block was performed at the T11–12 interspace followed by intrathecal neurolysis with 6% phenol in glycerin on a subsequent date. During both procedures, we used a tilting radiolucent orthopedic fracture table to maintain strict left lateral-supine positioning. A tilting orthopedic fracture table may be a valuable adjunct to ensure positional stability during intrathecal neurolysis.